Radiological and pathological correlation of a rare case of primary breast follicular lymphoma in a male patient, presenting as gynaecomastia. Issue 1 (21st April 2021) - Coughlan, Fionn; Rijhumal, Anmol; Dissanayake, Deepthi; Wylie, Elizabeth
Summary: We present an exceptionally rare case of primary breast follicular lymphoma in a male patient, who presented to us with gynaecomastia for investigation. To our knowledge there have only been two other cases published in the literature to date. In Western Australia, there have been no cases in at least the past 10 years. This particular case highlights the importance of radiological and pathological correlation in making the diagnosis, particularly in the assessment of breast lumps in a male patient, where imaging and clinical findings alone could not make the diagnosis.